Meta-Analysis and Systematic Review of the Comparison of Dynamic and Static Dry Needling Techniques for Myofascial Pain Syndrome Management Based on VAS Scale - Maranatha, Armando Vengo Subito Lewi; Warouw, Finny; Runtuwene, Theresia; Maja Pertiwi, Junita (Green Publisher Indonesia, 2025)
Myofascial Pain Syndrome (MPS) is a common musculoskeletal pain condition, often occurring in the trapezius muscle, and can lead to decreased function and quality of life for patients. MPS is frequently observed in individuals with poor posture or who engage in repetitive physical activities. Dry needling (DN) is one of the effective methods to address this pain, with two primary techniques: dynamic (peppering) and static. This study aims to compare the effectiveness of these two techniques in reducing pain in patients with MPS, using the VAS scale. The research design is a systematic review and meta-analysis of Randomized Controlled Trials (RCTs), which combines primary data to generate new evidence. The results indicate that static dry needling is more effective in reducing pain compared to the dynamic technique, although the difference is not statistically significant. The static technique resulted in a greater reduction in VAS scores, with a mean difference of -0.86 (95% CI: -2.47 to 0.75) and a p-value of 0.30. Although not significant, the static technique appears more stable, particularly for patients with high tissue sensitivity and low tolerance to needle manipulation. This study contributes to a deeper understanding of the effectiveness of both techniques and may serve as a foundation for further research and the application of more appropriate techniques in myofascial pain management.